Simulating gas-liquid mass transfer in a spin filter bioreactor (2015)
RESUMEN: Computational fluid dynamics (CFD) and population balance model (PBM) model have been used to simulate hydrodynamics and mass transfer in a 0.014 m3 Spin Filter Bioreactor. The operating conditions chosen were defined by typical settings used for culturing plant cells. Turbulence, rotating flow, bubbles breakage and coalescence were simulated by using the k-e, MRF (Multiple Reference Frame) and PBM approaches, respectively. The numerical results from different operational conditions are compared with experimental data obtained from measurements and good fitting data is achieved. Interested by these simulated and experimental results CFD simulations are qualified as a very promising tool not only for predicting gas-liquid hydrodynamics but also for finding design requirements that must be implemented to optimize an aerobic bioprocessing useful for plant cell culture applications which are characterized by the constrain of achieving relatively high mass transfer conditions and avoiding cellular damage due to hydrodynamic conditions.